ASPEK HUKUM TERHADAP TRANSAKSI PERDAGANGAN NARKOTIKA DI DAERAH PERBATASAN ANTARA REPUBLIK INDONESIA-MALAYSIA - Wanda Masfi Yolandi (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACT This study is entitled "LEGAL ASPECTS ON THE TRANSACTION OF NARCOTIC TRADING IN THE BORDER REGION BETWEEN THE REPUBLIC OF INDONESIA - MALAYSIA", under the guidance that I respect Mrs. Kunti Widayati, S.H., M.Hum as a Supervisor 1 and Mr. Sukindar, S.H., M.H as the Supervisor II.The purpose of this study is to find out clearly the legal aspects of Narcotics trade transactions in the border area between the Republic of Indonesia and Malaysia and aims to find out how the roles and responsibilities of Indonesia through BNN in handling and overcoming the circulation of Narcotics in the border area and legal actions for Narcotics dealers in the Indonesia - Malaysia border area.This research is a type of empirical normative research. Research location in Samarinda National Narcotics Agency. The type of data used is primary data sourced from BNN staff who directly handle Narcotics issues and secondary data obtained from library materials and regulations relating to the thesis title. Data collection techniques used are carried out with literature, study. Analysis of the data used is qualitative analysis, where the data collected will be analyzed through three stages, namely reducing data, presenting data and, concul.From the results of the study, it can be concluded that the efforts of the Government of Indonesia in combating drug trafficking from Malaysia are more focused on law enforcement efforts. This is done to cut off and eradicate cross-border drug networks. Of course, based on the origin of drugs come the majority from Malaysia who has direct borders on land and sea. However, the two countries still find difficulties in conducting a complete eradication. This is because there is still no ideal form of agreement between the two countries in terms of drug trafficking routes, as indicated by the lack of joint patrols by the two countries over land and sea routes in border areas and also to find out the Role of the National Narcotics Agency in Combating Abuse Drugs in the Indonesian-Malaysian Border. Keywords: The Role of DPRD of Samarinda City, Mechanism of Implementation and Supervision on Local Budget of Samarinda City Revenue